A Case of Ruptured Rudimentary Horn of Uterus during Pregnancy - U, Ruman; K, Khanam; S, Akhter; R, Karim (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
Pregnancy in a rudimentary horn of an unicornuate uterus is a rare and life threatening situation for mother and fetus. Usually pregnancy continues upto approximately 18-20 weeks of gestational age. Then it usually ruptures and severe haemorrhage ensues. Emergency laparotomy is the treatment of choice. Here we report a case of 36 years woman with secondary subfertility who has history of taking ovulation inducing drug. She presented with 20 weeks amenorrhoea with severe abdominal pain and hypovolemic shock. Urgent laparotomy was done and the diagnosis was confirmed. Bangladesh J Obstet Gynaecol, 2017; Vol. 32(2) : 121-123